Influence of ASE Noise on Performance of DWDM Networks Using Low-power Pumped Raman Amplifiers - Ninh, Bui Trung; Tuan, Nguyen Quoc; Hung, Ta Viet; Anh, Nguyen The; Hoi, Pham Van (Communications in Physics, 2015)
We present the results of investigation  for  influence of amplified spontaneous emission (ASE) noise, noise figure (NF) and  chromatic dispersion on the performance of middle-distance Dense-wavelength-division-multiplexing (DWDM) networks using low-power pumped distributed Raman amplifiers (DRAs) in two different pump configurations, i.e., forward and backward pumping. We found that the pumping configurations, ASE noise, and dispersion play an important role for improving network performance by decrease of noise figure and bit error rate (BER) of the system. Simulation results show that the lowest bit error rate and low noise figure were obtained, when using forward pumping configuration. Moreover, we have also compared ASE noise powers of the simulation with these of the experiment. These results conclude that DRA with low pump power  ($<1$~W) is the promising key technology for short-- and/or middle-distance DWDM transmission networks.